# Algebra - Simplify Expression

by Tabitha Smith
(Lousianna)

Simplify the expression:

(88n^(12)-66n^(7))/(11n^3)

There is more than one way to simplify this expression.

### Comments for Algebra - Simplify Expression

 Nov 03, 2011 Algebra - Simplify Expression by: Staff Question: by Tabitha Smith (Louisiana) (88n^(12)-66n^(7))/(11n^3) Answer: (88n¹² - 66n⁷)/(11n³) There is more than one way to simplify this expression, but dividing the problem into two separate fractions is probably the fastest. You can split the problem into two fractions, and then deal with each fraction separately. (88n¹² - 66n⁷) / (11n³) = (88n¹²) / (11n³) - (66n⁷) / (11n³) = [(8 * 11) * n¹²] / (11n³) - [(6 * 11) * n⁷) / (11n³)] = [(8 * n¹²) / n³] * (11 / 11) - [(6 * n⁷) / n³]) * (11 / 11) = [(8 * n¹²) / n³] * (1) - [(6 * n⁷) / n³]) * (1) = [(8 * n¹²) / n³] - [(6 * n⁷) / n³]) = [(8 * n⁹ * n³) / n³] - [(6 * n⁴ * n³) / n³]) = (8 * n⁹) * (n³ / n³) - (6 * n⁴) * (n³ / n³) = (8 * n⁹) * (1) - (6 * n⁴) * (1) = (8 * n⁹) - (6 * n⁴) = 8n⁹ - 6n⁴ The final answer is: 8n⁹ - 6n⁴ Thanks for writing. Staff www.solving-math-problems.com